ØªØÙ„ÙŠÙ„ Ø§Ù„Ø£Ø®Ø·Ø§Ø¡ Ø§Ù„Ù†ØÙˆÙŠØ© Ø§Ù„Ù„ØºÙˆÙŠØ© ÙÙŠ Ø§Ù„Ø®Ø·Ø§Ø¨Ø© Ø§Ù„Ù…Ù†Ø¨Ø±ÙŠØ© (Ø¯Ø±Ø§Ø³Ø© ØØ§Ù„ÙŠØ©) - Fadillah, Roojil (Maharaat: Jurnal Pendidikan Bahasa Arab, 2018)
This research is a continuation of the previous research but in different theme. This research aimed to enrich the existing literature within the said theme to aid non-Arab speakers in speaking Arabic, especially Nahwu (Syntax) errors. Site determination became important in this study. The researcher conducted the research in Islamic boarding school in Central Java which Arabic proficiency was good, namely Islamic Boarding School Al-Irsyad located in Semarang regency. Qualitative approach was used and was supported by numerical data to support the conclusion. Descriptive analysis method was also used to narrate the analysis. Data were collected through interview, unstructured dialogue, and recording using audio media. Research results showed that there were 56 conversational errors in the activities during Khutbah Ilmiah; there were 38 syntax errors, meaning that about 68% of errors occurred in syntax level. The causes were focused into 3 major points, namely first: speakers underestimated the rules (18%), second: speakers do not know the rules (34%), third: the intervention rate of occurrence of error was 18%.Â Â